Mental Health and Older Adults: A Narrative Synthesis of the Literature - Villafuerte, Salvacion Laguilles (Universitas Ahmad Dahlan, 2024)
The older adult population has been a growing concern in the global context calling for attention to aging processes, supportive measures and health care policies. In the Philippines, the population of older people is accumulating swiftly with a faster growth compared to the total population of the country. Thus, this calls for a closer attention on the overall wellness and the mental health of older adults that are more crucial in comparison to other ages in one’s lifetime. Generating a database search strategy for the last 10 years focused on the mental health of older adults, retrieved articles from APA PsycNet, ProQuest, SAGE, EBSCOHost and PubMed Central electronic databases were synthesized guided by the set inclusion and exclusion criteria and utilizing the PRISMA flowchart of the record selection process. This narrative synthesis rendered the Mental Health Orientations of Older Adults to illustrate an integrated framework to understand mental health and older adults.The findings of this research synthesized a portrait on how older adults give credence to their mental health in various concerns and needs which they directly and indirectly experience. These will be valuable in considering age-specific mental health needs aligned with the three orientations considering Philippine law provisions on mental health (RA11036 or the Mental Health Act) and on senior citizens (RA9994 or the Expanded Senior Citizen Act) in the continuing aim of providing access for mental health services and integrated mental health promotion strategies for the older adult population.